Parenting Typification and Motive of Working Mothers in Accompanying Children’s Distance Learning in Indonesia During The Covid-19 Pandemic - Sinuraya, Veny Florencia; Putra, Afdal Makkuraga; Aunul, Sofia; Tomohardjo, Irmulansati (Komunitas: International Journal of Indonesian Society and Culture, 2024)
The government’s determination of the pandemic status of COVID-19 has changed almost all lines of people’s lives, from the economy, and health infrastructure, to education. The rapid transmission of COVID-19 cases has made the government implement Distance Learning (DL) at all school levels, including elementary school levels. The implementation of DL makes elementary school children potentially experience learning loss. On the other hand, working mothers who are used to handing over educational matters to schools find it difficult to accompany children’s DL at home. Therefore, this study aims to determine the typification of parenting carried out by working mothers in accompanying children’s distance learning during the COVID-19 pandemic. The case study method was used in conjunction with a qualitative descriptive research design. The researchers gathered primary data by interviewing five informants, all of whom were working mothers, as well as one psychologist. The findings revealed that women employ monopoly communication patterns while speaking with their children; mothers are perceived as authorities who make ultimate judgments. Furthermore, helpful and sympathetic communications are used by working mothers. Researchers found three characteristics of working mothers’ care during the pandemic, namely over- empathy, life vest, and supportive.